2022
DOI: 10.1038/s41467-022-31753-y
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of 45 large-scale wastewater sites in England to estimate SARS-CoV-2 community prevalence

Abstract: Accurate surveillance of the COVID-19 pandemic can be weakened by under-reporting of cases, particularly due to asymptomatic or pre-symptomatic infections, resulting in bias. Quantification of SARS-CoV-2 RNA in wastewater can be used to infer infection prevalence, but uncertainty in sensitivity and considerable variability has meant that accurate measurement remains elusive. Here, we use data from 45 sewage sites in England, covering 31% of the population, and estimate SARS-CoV-2 prevalence to within 1.1% of e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…This study provides a necessary foundation for investigating the link between wastewater and COVID-19 prevalence at any desired spatial resolution. A previous study ( Morvan et al, 2022 ) considered the relationship between wastewater concentration and COVID-19 prevalence using the ONS-CIS survey and testing data on 45 STW catchment areas over the period July 2020 to March 2021. Specifying a spatio-temporal Bayesian model, they reported an overall good correspondence between the wastewater concentration and prevalence, concluding that wastewater can be used to provide reliable estimates of COVID-19 infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides a necessary foundation for investigating the link between wastewater and COVID-19 prevalence at any desired spatial resolution. A previous study ( Morvan et al, 2022 ) considered the relationship between wastewater concentration and COVID-19 prevalence using the ONS-CIS survey and testing data on 45 STW catchment areas over the period July 2020 to March 2021. Specifying a spatio-temporal Bayesian model, they reported an overall good correspondence between the wastewater concentration and prevalence, concluding that wastewater can be used to provide reliable estimates of COVID-19 infections.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, they found that a decline in the wastewater virus concentration preceded by two to four days the reduction in community cases after lockdown measures were implemented. More recently, Morvan et al (2022) analysed data from 45 STWs across England between July 2020 and March 2021. Using multilevel modelling they reported that wastewater samples can be used to predict COVID-19 prevalence, with a lead time of four to five days.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for each subject in our serosurvey, we estimated the probability of being infected by SARS-CoV-2 before study recruitment, given age, vaccination record and seropositivity of the serum sample (see Methods). We assumed that: (i) daily age-specific force of infection was proportional to daily viral load from city-wide wastewater surveillance (see Figure 1) which has been shown to be a robust (normalized) proxy for disease prevalence over time [2][3][4]; and (ii) one-dose vaccination provided no protection against infection and each successive homologous dose conferred greater VE which decayed exponentially over time at the same rate between doses of the same vaccine [5].…”
Section: Main Textmentioning
confidence: 99%
“…More specifically, they found that a decline in the wastewater virus concentration preceded by two to four days the reduction in community cases after lockdown measures were implemented. More recently, Morvan et al (2022) analysed data from 45 STWs across England between July 2020 and March 2021. Using a multilevel modelling approach they reported that wastewater samples can be used successfully to predict COVID-19 prevalence, with a lead time of four to five days.…”
Section: Introductionmentioning
confidence: 99%